FILM ANIMASI 2D (DIMENSI) PENYULUHAN KB - Tri Hidayatul Ahmad Ismail (Universitas Amikom Purwokerto, 2013)
Multimedia Animation is an attempt to make a live presentation of static or moving, the animation may consist of images and music to blend together and become alive. In this case Multimedia Animation designed by using multimedia-based information technology. From year to year Multimedia Animation Film Animation shaped more advanced, both in coloring, and in concep movement. With the community Animation Film spoiled by progress dazzling animation creation. Later in the era of globalization in Indonesia's population penetration rate can be calculated very rapidly. So the authors designed an Animated Film to Family Planning Counseling to promote family planning in the community.Data collection methods used to make this application is the method of interview and literature study. For the development of the system in this paper by using development techniques Luther systems development models - Sutopo which consists of six stages: concept, design, collecting materials, assembly, testing and distribution. The results of this study are 2D Animation Film as a medium of socialization to Family Planning Department with extension. Avi and will be distributed via CD media and aired on Social Media such as Facebook, Twitter and YouTube. This animation movie aims to be one choice as the media reduces the increase in the number of residents is too drastic. Keywords: movies, animation, family planning, Luther-Sutopo